Lifelong multi-agent pathfinding with online tasks - Tay, David Ang Peng (Nanyang Technological University, 2023)
The Multi-Agent Pathfinding (MAPF) problem involves finding optimal or near-optimal paths for multiple agents in a shared environment while avoiding collisions and conflicts. However, traditional MAPF is limited in its ability to handle real-life scenarios, such as automated warehouses, where agents face a continuous stream of tasks. To address this, we investigate the Multi-Agent Pickup and Delivery (MAPD) problem, which requires agents to complete tasks in an online, lifelong manner where tasks are added dynamically.